2018
DOI: 10.2355/isijinternational.isijint-2017-644
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microstructure and Chemical Composition of Deadman Coke of a 2800 m<sup>3</sup> Industrial Blast Furnace

Abstract: The paper examined the changes in microstructure and inorganic elements in their true mineral forms of the coke samples from various hearth locations using X-ray diffraction (XRD) and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) after the blow out and cool down of a 2 800 m 3 industrial blast furnace. The results illustrate that all deadman coke samples from fines to lumps were confirmed to be highly graphitized. Furthermore, the deadman coke was filled up with the accumulated KAlSiO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Previous studies on hearth coke behaviors have focused on coke graphitization, mineral transformation, mineral yield, open porosity and microstructure, etc., through the dissection of furnace after blow-out. [10][11][12][13][14] Although the information of the particle size distribution of deadman coke and deadman porosity is critical for understanding the blast furnace hearth phenomenon, the relevant study is rare and insufficient. Jiao et al investigated the mean size of hearth coke using image-processing technique and found the hearth coke size was about 32 mm-34 mm.…”
Section: Analysis Of the Coke Particle Size Distribution And Porositymentioning
confidence: 99%
“…Previous studies on hearth coke behaviors have focused on coke graphitization, mineral transformation, mineral yield, open porosity and microstructure, etc., through the dissection of furnace after blow-out. [10][11][12][13][14] Although the information of the particle size distribution of deadman coke and deadman porosity is critical for understanding the blast furnace hearth phenomenon, the relevant study is rare and insufficient. Jiao et al investigated the mean size of hearth coke using image-processing technique and found the hearth coke size was about 32 mm-34 mm.…”
Section: Analysis Of the Coke Particle Size Distribution And Porositymentioning
confidence: 99%
“…The KAlSiO 4 observed in the skull may be attributed to the fact that KAlSiO 4 deposited in the deadman coke enters into the blast furnace slag with the dissolution of coke carbon into hot metal. 30)…”
Section: Microstructure Analysis Of Skull At the Level Of Layermentioning
confidence: 99%
“…Then the blast furnace slag that penetrated into the pores of the coke is also brought into the salamander indirectly. 30) With the dissolution of deadman coke into hot metal, the blast furnace slag in the deadman coke is exposed and attached to the hot surface of the carbon brick below the taphole level under the suitable conditions to form skull, protecting blast furnace linings from erosion. 30) Accordingly, the Ca 2 Al 2 SiO 7 and Ca 2 MgSi 2 O 7 in the skull are derived from blast furnace slag in deadman coke, rather than the ash in the feed coke.…”
Section: Microstructure Analysis Of Skull At the Level Of Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the coke in the iron layer below the taphole centerline and the interaction between coke and hot metal was not studied. Niu et al 11) studied the coke mineral phase and the microstructure of hearth deadman coke in a blast furnace hearth. They thought that the final slag can permeate into the coke pores and react with coke minerals.…”
Section: Coke Microstructure and Graphitization Across The Hearth Deamentioning
confidence: 99%